Peculiarities of producing and measuring circular scales - Sabaitis, Deividas; Giniotis, Vytautas; Rybokas, Mindaugas; Dmitrijev, Gintaras (Geodesy and Cartography, 2011)
The paper deals with investigation into manufacturing circular scales and its accuracy evaluation methods and means considering the new development of production and measurement methods based on advancing laser instruments. The article describes the results of recently conducted analysis and presents initial trials of applying them in practice.Apskritiminių skalių gamyba, matavimo ypatumaiSantrauka. Supažindinama su apskritiminių skalių tyrimais, gamybos ypatumais ir matavimo būdais. Įvertinamas naujų gamybos ir matavimo metodų plėtotės lazerinių prietaisų pagrindu lygis. Pristatomi kai kurie pastarųjų metų darbai ir pradiniai jų taikymo bandymai.Reikšminia žodižiai: kampas, apskritiminės skalės, lazerinis matavimas.Oсобенности производства и измерения круговыx шкалРезюме. Статья посвящена исследованию методов и средств производствa круговыx шкал и оценке методов иx точности с учетом новых развитий производства и измерений, основанныx на разработкax лазерныx инструментов. Представлены некоторые последние разработки и первичные испытания по их применению.Ключевые слова: угол, круговые шкалы, перемещение, определение, лазерные измерения.